VD_FINDINFO HC / 2024 / 445 vom 12. Juni 2024 - VD Tribunal cantonal (2024)
CHOSE JUGÉE, REJET DE LA DEMANDE, NOUVEAU MOYEN DE FAIT, MESURE PROVISIONNELLE, SALAIRE | 179 al. 1 CC, 317 al. 1 CPC (CH), 328 al. 1 let. a CPC (CH)